Sustained virological response to ombitasvir/paritaprevir/ritonavir and dasabuvir treatment for hepatitis C: Real‐world data from a large healthcare provider. Issue 2 (7th November 2017) - Weil, C.; Mehta, D.; Koren, G.; Pinsky, B.; Samp, J. C.; Chodick, G.; Shalev, V.
Summary: Treatment with ombitasvir/paritaprevir/ritonavir and dasabuvir, with or without ribavirin (OPrD ± RBV), was the first interferon‐free direct‐acting antiviral for hepatitis C virus (HCV) introduced to Israel's national basket of health services in February 2015. Patients with HCV genotype 1 (GT1) and advanced fibrosis (F3‐F4) were eligible for treatment in 2015. This study aimed to characterize patients initiating OPrD ± RBV and assess sustained virological response (SVR). A retrospective cohort study was performed using the database of Maccabi Healthcare Services (MHS), a 2‐million‐member health plan in Israel. The study population included adults who initiated OPrD ± RBV through December 2015 per health basket criteria. A gap in medication fills (>14 days between a fill's run‐out and the next fill) was used to estimate adherence. SVR was defined by the viral tests at least 12‐week post‐treatment. The study population consisted of 403 patients (56.3% male), with a mean age of 60.7 years (SD 11.0). Overall, 71.0% were naïve to prior HCV treatment, and 95.6% were treated with a 12‐week regimen. A total of 348 patients (86.4%) completed the regimen in the usual time frame (highly adherent), whereas 8.2% completed with a gap, and 4.7% purchased less than the recommended dose. SVR rates overall and among highly adherent patients were 395/403 (98.0%; 95% CI 96.1‐99.1) and 346/348 (99.4%; 95% CI 97.9‐99.9), respectively. GT1b patients on 12‐week regimens attained SVR rates of 194/196 (fibrosis F3) and 170/176 (cirrhosis). After a first year of provision of OPrD ± RBV with good adherence, high SVR rates were achieved in various patient subgroups and comorbidities.